FSCN1 Promotes Radiation Resistance in Patients With PIK3CA Gene Alteration - Li, Sisi; Huang, Xiao-ting; Wang, Meng-yao; Chen, Dong-ping; Li, Ming-yi; Zhu, Yan-yi; Yu, Yi; Zheng, Lu; Qi, Bin; Liu, Jin-quan (Frontiers in Oncology, 2021)
Radiotherapy is one of the standard treatments for cervical squamous cell carcinoma and head and neck squamous cell carcinoma. However, the clinical efficacy of this treatment is limited by radioresistance. The discovery of effective prognostic biomarkers and the identification of new therapeutic targets have helped to overcome the problem of radioresistance. In this study, we show that in the context of PIK3CA mutation or amplification, high expression of fascin actin-bundling protein 1 (FSCN1) (using the median as the cut-off value) is associated with poor prognosis and radiotherapy response in cancer patients. Silencing FSCN1 enhances radiosensitivity and promotes apoptosis in cancer cells with PIK3CA alterations, and this process may be associated with the downregulation of YWHAZ. These results reveal that FSCN1 may be a key regulator of radioresistance and could be a potential target for improving radiotherapy efficacy in cervical squamous cell carcinoma and head and neck squamous cell carcinoma patients with PIK3CA alterations.